Генетический контроль морфологических особенностей листьев Arabidopsis thaliana (L.) heynh. - Кирпичёва, И.В. (Фактори експериментальної еволюції організмів, 2010)
При сумісній дії в димутанта an1,an3 формується розеткове листя довгастої форми. Рецесивні мутації as1-1 і cp3-1 зменшують відношення довжини листової пластинки до її ширини. При їх спільній дії відношення довжини листової пластинки до її ширини виявляється менше 1, так що лист можна вважати не округлим, а широким. При совместном действии у димутанта an1,an3 формируются розеточные листья продолговатой формы. Рецессивные мутации as1-1 и cp3-1 уменьшают отношение длины листовой пластинки к её ширине. При их совместном действии отношение длины листовой пластинки к её ширине оказывается меньше 1, так что лист можно считать не округлым, а широким. It was stated that mutant аллели of an1-1 and an3-1 is increased by attitude oflength of sheet plate toward its width. Interaction of genes AN1 and AN3 results in formingof rosette-like leaves of oblong form an1,an3. The recession mutations of as1-1 and cp3-1diminish attitude of length of sheet plate toward its width. At united their action attitudeof length of sheet plate toward its width appears less than 1, so that a sheet can be con-sidered not rounded, but wide.